2010
DOI: 10.1121/1.3298431
|View full text |Cite
|
Sign up to set email alerts
|

Using air-coupled sensors to determine the depth of a surface-breaking crack in concrete

Abstract: Previous studies showed that the surface wave transmission coefficient across a surface-breaking crack in concrete can be used to estimate the crack depth. However, inconsistencies in the surface wave transmission measurements limit the test accuracy and application of this technique. The inconsistencies come from near-field scattering by the crack tip and inconsistent sensor coupling conditions on rough concrete surfaces. This study first investigates the near-field size based on numerical analyses, and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 20 publications
2
38
0
6
Order By: Relevance
“…Variation in the phase velocity would be an indication of the variation of material properties with depth. Surface wave based methods have also shown good potential in vertical crack characterization (Kee and Zhu, 2010). One of the devices for USW testing, the portable seismic property analyzer (PSPA), is shown in Figure 2.…”
Section: Bridge Deck Deterioration and Ndt Methodsmentioning
confidence: 99%
“…Variation in the phase velocity would be an indication of the variation of material properties with depth. Surface wave based methods have also shown good potential in vertical crack characterization (Kee and Zhu, 2010). One of the devices for USW testing, the portable seismic property analyzer (PSPA), is shown in Figure 2.…”
Section: Bridge Deck Deterioration and Ndt Methodsmentioning
confidence: 99%
“…To estimate crack depth using the transmission of surface waves, Angel and Achenbach [60] proposed theoretical solutions for the transmission and reflection of surface waves across a single crack with regard to the normalized crack depth (crack depth divided by wavelength). Transmission coefficients are applied to determine the crack depth in concrete [61,62,63,64]. Significant differences are not observed between transmission coefficients in artificial single cracks generated by notches and real cracks generated by three-point bending tests [61].…”
Section: Applicability and Limitation Of Ultrasonic Methodsmentioning
confidence: 99%
“…An effective solution of this problem is the use of contact-less sensors. Previous researchers have demonstrated that air-coupled sensors are effective in improving signal consistency and test speed in measurements of leaky surface waves in concrete and other solid materials [4,5,6]. In addition, air-coupled sensors were implemented in an IE test setup for evaluating various defects (delaminations with various sizes and depths, and volumetric defects) in concrete slab in laboratory [7,8].…”
Section: Introductionmentioning
confidence: 99%